Effect of microbial fertilizers on soil microbial community structure in rotating and continuous cropping Glycyrrhiza uralensis - Qiu, Daiyu; Wang, Xue; Jiang, Kan; Gong, Gaoxia; Bao, Fang (Frontiers in Plant Science, 2025)
IntroductionGlycyrrhiza uralensis is a perennial medicinal plant. It’s generally cultivated for three years, and should avoid long-term continuous cultivation. However, unreasonable crop rotation and extensive fertilization are common in G. uralensis cultivation, which leads to the imbalance of soil microflora structure, and the obstacle of continuous cropping are becoming increasingly serious. Some microbial fertilizers such as Bacillus amyloliquefaciens, Bacillus subtilis, and complex microbial agent have the advantage of regulating soil microbial community structure and improving the soil environment. Therefore, these three kinds of microbial fertilizers were applied to G. uralensis and their effects on soil microorganisms of G. uralensis were studied.MethodsCombine microbial fertilizers with conventional fertilization for continuous cropping and rotating G. uralensis. High-throughput sequencing technology was used to determine soil microbial richness, diversity and distribution of community structure in rotating and continuous cropping G. uralensis.Results and discussionContinuous cropping reduced G. uralensis soil bacterial diversity by 7.56% and increased fungal richness by 17.01% compared with crop rotation. However, after the application of microbial fertilizers, the fungal richness and diversity of continuous cropping G. uralensis were significantly reduced by 4.76%~20.96%, and the soil bacterial diversity of continuous cropping and rotating G. uralensis was significantly increased by 7.22%~12.03% and 6.75%~11.69% compared with the respective controls, respectively. Continuous cropping and rotating G. uralensis soil dominant bacteria mainly include Proteobacteria, Actinobacteria and Gemmatimonadota, and the dominant fungi include Ascomycota, Basidiomycota and Zygomycota. The activity process of these microbial communities was mainly through carbohydrate metabolism and amino acid synthesis pathway in metabolism. The complex microbial agent significantly increased the relative abundance of soil dominant bacteria communities of continuous cropping and rotating G. uralensis by 3.11~11.54 percentage points, and significantly reduced the relative abundance of soil dominant fungal communities of continuous cropping G. uralensis by 1.57~8.93 percentage points, compared with the control. Of the three microbial fertilizers, the complex microbial agent had the most significant effects on optimizing the soil microbial community structure of continuous cropping and rotating G. uralensis. Conclusion: the application effect of different microbial fertilizers in continuous cropping G. uralensis was better than crop rotation, and the application effect of complex microbial agent was the best, which has more application value and development prospect in the cultivation management of G. uralensis.